Preconception period in women and men undergoing Assisted Reproduction: A gender approach for reproductive health. (August 2022) - Cirillo, Michela; Coccia, Maria Elisabetta; Dimmito, Arianna; Fatini, Cinzia
Highlights: A link between infertility and cardiovascular health exists for both women and men. Preconception health in men is underestimated. Couples had a poor preconception health and unfavourable cardiovascular risk profile. Women showed a closer adherence to Mediterranean diet in comparison to men. ART offers an opportunity to evaluate cardiovascular profile and lifestyle factors. Abstract: Objective: To evaluate lifestyle and risk factors playing a role in increasing the burden of cardiovascular diseases and to increase attention of clinicians who should envision a broader preconception approach in ART, not only in women but also in men. Study design: In this cross-sectional study we investigated 90 Caucasian couples, referred to the Internal Medicine Clinic at the Assisted Reproductive Technology Centre, in order to better define in preconceptional period their cardiovascular risk profile, based on metabolic parameters and lifestyle behaviours. Results: We observed two-fold increase of overweight in men in comparison to women (p = 0.006). Values of waist ≥ 94 cm in men and ≥ 80 cm in women were present in 53.3% of men and 32.2% of women (p = 0.007). Similarly, values of WHR according to gender cut-off, were present in 64.4% of men and in 32.2% of women (p < 0.0001). In men we observed a significantly higher prevalence of hypertension (p = 0.02), significantly lower HDL-c (p = 0.001) and higher levels of total cholesterol (p = 0.01), LDL-c and triglycerides (p = 0.001). Sedentary behaviour was observed in about 60% of both genders. Alcohol consumption was reported by 42.2% of men and 26.7% of women (p = 0.04) and smokers were more prevalent among women (26.7%) than men (24.4%). We observed a lower adherence to Mediterranean Diet related to consumption of red meat and meat products (p = 0.02), as well as of legumes consumption (p = 0.01) in men, whereas sweet/pastries (p = 0.05) and fruits (p = 0.06) in women. Men and women with normal BMI, waist and WHR, showed a higher Mediterranean diet adherence in comparison to overweight/obese study population(p < 0.001). Finally, higher education level predicted the higher Mediterranean diet adherence in both gender (p = 0.01 for men, p = 0.03 for women). Conclusions: This study paid attention on preconceptional health in couples planning ART. Women have a greater biological role in childbearing, whereas the role of men is underestimated. The need to conceive through ART offers a window of opportunity not only to evaluate cardiovascular profile and lifestyle factors in couples prior to conception, but also to manage comorbidities and promote health behaviours in order to improve fertility and health outcomes in both women and men at short and long-term.